Stable landings mask irreversible community reorganizations in an overexploited Mediterranean ecosystem. Issue 12 (22nd November 2022) - Sguotti, Camilla; Bischoff, Aurelia; Conversi, Alessandra; Mazzoldi, Carlotta; Möllmann, Christian; Barausse, Alberto
Abstract: Cumulative human pressures and climate change can induce nonlinear discontinuous dynamics in ecosystems, known as regime shifts. Regime shifts typically imply hysteresis, a lacking or delayed system response when pressures are reverted, which can frustrate restoration efforts. Here, we investigate whether the northern Adriatic Sea fish and macroinvertebrate community, as depicted by commercial fishery landings, has undergone regime shifts over the last 40 years, and the reversibility of such changes. We use a stochastic cusp model to show that, under the interactive effect of fishing pressure and water warming, the community reorganized through discontinuous changes. We found that part of the community has now reached a new stable state, implying that a recovery towards previous baselines might be impossible. Interestingly, total landings remained constant across decades, masking the low resilience of the community. Our study reveals the importance of carefully assessing regime shifts and resilience in marine ecosystems under cumulative pressures and advocates for their inclusion into management. Abstract : Using novel methodology to investigate the presence of regime shifts in the Northern Adriatic Sea marine community, this work provides evidence of probably‐irreversible changes over the last 40 years connected to fishing pressure and climate change. Understanding these discontinuous dynamics is important in managing our oceans sustainably under climate change.